Patient participation during and after a self-management programme in primary healthcare – The experience of patients with chronic obstructive pulmonary disease or chronic heart failure. Issue 6 (June 2018) - Luhr, Kristina; Holmefur, Marie; Theander, Kersti; Eldh, Ann Catrine
Highlights: Patient participation is facilitated by equality and means for sharing and discussing. Patient participation is influenced by individuals' willingness to share and learn. Self-management programmes in primary care may enhance patient participation. Abstract: Objective: Patient participation is facilitated by patients' ability to take responsibility for and engage in health issues. Yet, there is limited research as to the promotion of these aspects of patient participation in long-term healthcare interactions. This paper describes patient participation as experienced by patients with chronic obstructive pulmonary disease (COPD) or chronic heart failure (CHF); the aim was to describe if and how a self-management programme in primary healthcare influenced patient participation. Methods: Patients who had participated in a self-management programme were interviewed in nine focus groups (36 patients). Data was analysed using qualitative content analysis. Results: Patients described equality in personal interactions, opportunities to share and discuss, and a willingness to share and learn to facilitate patient participation in a self-management programme. Consequently, patient participation was promoted by a match between the individuals' personal traits and the context. Conclusion: Features facilitating patient participation by means of sharing and assimilating knowledge and insights should be included in self-management programmes and in the care for patients with COPD and CHF. Practice implications: A self-management programme can complement regular primary care regarding enhanced understanding of one's disease and support patient participation and the patient's own resources in self-management.